2015
DOI: 10.1007/jhep12(2015)116
|View full text |Cite
|
Sign up to set email alerts
|

Holographic thermalization in a top-down confining model

Abstract: It is interesting to ask how a confinement scale affects the thermalization of strongly coupled gauge theories with gravity duals. We study this question for the AdS soliton model, which underlies top-down holographic models for Yang-Mills theory and QCD. Injecting energy via a homogeneous massless scalar source that is briefly turned on, our fully backreacted numerical analysis finds two regimes. Either a black brane forms, possibly after one or more bounces, after which the pressure components relax accordin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 52 publications
8
39
1
Order By: Relevance
“…The time scale at which a given quantity approaches the value that it takes in a thermal state (with temperature determined by the energy of the initial nonequilibrium state) is called the thermalization time associated with the observable. In many situations, in the context of holography, it has been found that expectation values of local operators, which we will call one-point functions, approach their thermal values with rates dictated by the lowest quasinormal mode of the corresponding bulk field (see [1,2] for two examples demonstrating this point). Phrased in field theory language, the time scale on which one-point functions thermalize, starting from a far-from-equilibrium state, is the same on which infinitesimally small perturbations away from thermal equilibrium decay back to equilibrium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time scale at which a given quantity approaches the value that it takes in a thermal state (with temperature determined by the energy of the initial nonequilibrium state) is called the thermalization time associated with the observable. In many situations, in the context of holography, it has been found that expectation values of local operators, which we will call one-point functions, approach their thermal values with rates dictated by the lowest quasinormal mode of the corresponding bulk field (see [1,2] for two examples demonstrating this point). Phrased in field theory language, the time scale on which one-point functions thermalize, starting from a far-from-equilibrium state, is the same on which infinitesimally small perturbations away from thermal equilibrium decay back to equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…The computation of this quantity requires the knowledge of the Wightman two-point function. 2 The definition was inspired by the fluctuation dissipation relation in a thermal state and has already been used earlier in the context of nonequilibrium quantum field theory (see e.g. [15]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been a growing interest in studying the quantum quenches in the confined phase (see e.g. [30][31][32]), where they have found some evidence that the equilibrium (formation of a black hole in the gravity side) may not be the final fate of a system driven far from equilibrium by applying a quench. In this regard, it would be interesting to study the evolution of a confining theory like the one in the present paper under electric field quenches, as an important class of quenches.…”
Section: Discussionmentioning
confidence: 99%
“…This process appears to repeat for as long as the numerical routines of [5] were able to run. Recently, analogous calculations were performed in the AdS soliton background [6] which is qualitatively similar to the hardwall in that there is a mass gap for black brane formation in the bulk. There too perturbations were identified which appear to scatter indefinitely, while others lead to collapse and black-brane formation.…”
Section: Icnfp 2015mentioning
confidence: 93%